Penanaman Nilai-Nilai Tasawuf dalam Pembinaan Akhlak - Susanti, Agus (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Education is all efforts to maintain and develop human nature both esoteric and exoteric aspect. The reality in the world of education shows that the esoteric aspects of human progress lag far behind the exoteric aspect. The false paradigm that limits religious studies at the madrasah or pesantren institution alone, will slowly alienate public school students from the planting of faith and piety. As a result, the orientation of educational change is becoming increasingly materialistic, individualistic, and secularistic. Thus occurred the massive reduction of human existence itself.               To overcome this, the need to reorient education towards a holistic education with value investment Sufism to draw closer to Allah through Islam amaliah amaliah-religious school. By this, it will create vertical integration dimension of submission to God and dialectical dimension horizontally towards each other and the environment. Integration produces an output in the form of student personality education righteous and noble behavior. Then it can be understood Sufism is very important and can not be separated from solving the problems of education.